Industrial Structure, Environmental Pressure and Ecological Resilience of Resource-Based Cities-Based on Panel Data of 24 Prefecture-Level Cities in China - Chen, Yating; Wang, Hongmei (Frontiers in Environmental Science, 2022)
Based on 432 data sets from three resource-based provinces, Anhui, Shanxi, and Sichuan, a fixed-utility model was established using panel data for empirical analysis to investigate the relationship between industrial structure, environmental pressure, and ecological resilience of resource-based cities, using entropy value method and principal component analysis to measure the industrial structure, environmental pressure and ecological resilience of resource-based cities. It is found that for resource-based cities, the economic growth mainly relies on the development of the secondary industry, which is primarily dependent on local natural resources. The empirical results show that the regional industrial structure has a significant negative impact on the cities' ecological resilience, and the regional industrial structure has a significant positive effect on their environmental pressure. Based on the conclusion, policy recommendations are proposed to accelerate the upgrading of industrial structure and strengthen environmental policies in resource-based cities to improve urban ecological resilience.